Best Paper Selection (Yearbook of Medical Informatics, 2021)
Jin Q, Tan C, Chen M, Liu X, Huang S. Predicting clinical trial results by implicit evidence integration. https://arxiv.org/abs/2010.05639Poerner N, Waltinger U, Schütze H. Inexpensive Domain Adaptation of Pre-trained Language Models: Case Studies on Biomedical NER and Covid-19 QA. https://arxiv.org/abs/2004.03354Ive J, Viani N, Kam J, Yin L, Verma S, Puntis S, Cardinal R, Roberts A, Stewart R, Velupillai S. Generation and evaluation of artificial mental health records for Natural Language Processing. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7224173/